The Role of Carboxiangiography for the Diagnosis of Critical Limb Ischemia - Tursunov Jakhongir Tojiboevich, (Asian Journal of Pharmaceutical Research and Development, 2025)
Critical Limb Ischemia (CLI), the most severe manifestation of peripheral arterial disease, represents a growing global health challenge associated with significant morbidity, risk of limb loss, and mortality. Prompt and accurate vascular imaging is essential for diagnosis, treatment planning, and revascularization in CLI. However, the widespread use of iodinated contrast media in conventional angiography poses a considerable risk of contrast-induced nephropathy, particularly in patients with chronic kidney disease or diabetespopulations disproportionately affected by CLI. Carboxyangiography, which utilizes carbon dioxide (CO₂) as a contrast agent, has emerged as a safe, non-nephrotoxic alternative for vascular imaging. CO₂’s favorable physical properties—low viscosity, high solubility, and rapid pulmonary clearancemake it suitable for visualizing infra-diaphragmatic arterial lesions without compromising renal function. Clinical studies have demonstrated its diagnostic utility in detecting femoropopliteal and infrapopliteal arterial occlusions, with image quality sufficient for endovascular decision-making. While challenges such as limited use in supra-diaphragmatic vessels and operator dependency remain, advancements in delivery systems and imaging techniques continue to expand its applicability. This review explores the principles, clinical efficacy, safety profile, and current limitations of carboxyangiography in CLI, emphasizing its growing relevance in modern vascular diagnostics and its potential for broader integration into clinical practice.